2011
DOI: 10.1371/journal.ppat.1002068
|View full text |Cite
|
Sign up to set email alerts
|

Acquisition of Human-Type Receptor Binding Specificity by New H5N1 Influenza Virus Sublineages during Their Emergence in Birds in Egypt

Abstract: Highly pathogenic avian influenza A virus subtype H5N1 is currently widespread in Asia, Europe, and Africa, with 60% mortality in humans. In particular, since 2009 Egypt has unexpectedly had the highest number of human cases of H5N1 virus infection, with more than 50% of the cases worldwide, but the basis for this high incidence has not been elucidated. A change in receptor binding affinity of the viral hemagglutinin (HA) from α2,3- to α2,6-linked sialic acid (SA) is thought to be necessary for H5N1 virus to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
237
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4
1

Relationship

3
6

Authors

Journals

citations
Cited by 202 publications
(253 citation statements)
references
References 63 publications
(95 reference statements)
7
237
0
Order By: Relevance
“…Previously, it was proposed that isolates having isoleucine at residue 151 of the HA1 protein might be involved in different receptor binding (Claas et al, 1998). Recently, it was shown that deletion of RBD 129S combined with I151T increased α2-6 SA binding (Watanabe et al, 2011). It was observed that the pigeon strain isolated in this study has these substitutions.…”
Section: Discussionmentioning
confidence: 50%
“…Previously, it was proposed that isolates having isoleucine at residue 151 of the HA1 protein might be involved in different receptor binding (Claas et al, 1998). Recently, it was shown that deletion of RBD 129S combined with I151T increased α2-6 SA binding (Watanabe et al, 2011). It was observed that the pigeon strain isolated in this study has these substitutions.…”
Section: Discussionmentioning
confidence: 50%
“…A list of amino acid substitutions of biological relevance for mammalian adaptations or reducing drug susceptibility was investigated for the three reassortant isolates (Table 1). Although the most well-known receptor binding sites (222 to 224, H5 numbering) were still avian-like (QSG) in the three reassortant isolates (21), other mutations that may alter receptor specificity were detected, such as S123P, I151T, and T156A (22)(23)(24). The reassortant C isolates carried a deletion at position 126 in the HA, adding a potential N-glycosylation at site 124.…”
Section: Resultsmentioning
confidence: 99%
“…Viruses and Cells-Influenza virus strains A/crow/Kyoto/ 53/04 (H5N1) (Cw/Ky (H5N1)) and A/chicken/Egypt/CL6/07 (H5N1) (Ck/Eg (H5N1)) were isolated from embryonated chicken eggs inoculated with tracheal or lung homogenates from dead crows (10) or dead chickens (11), respectively. A/Beijing/262/95 (H1N1) (Beijing (H1N1)), A/Duck/Hong Kong/ 273/78 (H2N2) (Dk/Hk (H2N2)), A/Panama/2007/99 (H3N2) (Panama (H3N2)), A/Duck/Hong Kong/668/79 (H4N5) (Dk/ Hk (H4N5)), A/Duck/Hong Kong/820/80 (H5N3) (Dk/Hk (H5N3)), A/Turkey/Ontario/7732/66 (H5N9) (Tk/Ont (H5N9)), A/Duck/Hong Kong/960/80 (H6N2) (Dk/Hk (H6N2)), A/wigeon/ Osaka/1/01 (H7N7) (Wg/Os (H7N7)), A/Turkey/Ontario/6118/67 (H8N4) (Tk/Ont (H8N4)), and A/Duck/Hong Kong/448/78 (H9N2) (Dk/Hk (H9N2)) were kind gifts from Yoshinobu Okuno (Kanonji Institute, the Research Foundation for Microbial Diseases of Osaka University, Kagawa, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…The HA sequences of A/Thailand/ Kan353/04 (H5N1) (Thailand (H5N1)), A/Indonesia/5/05 (H5N1) (Indonesia (H5N1)), and A/Shanghai/1/06 (H5N1) (Shanghai (H5N1)) were constructed by PCR using overlapping deoxyoligonucleotides corresponding to the published sequence of the HA open reading frame. The full-length sequences of both A/duck/Egypt/D1Br/2007 (H5N1) (Dk/Eg (H5N1)) (clade 2.2.1) (PB2, PB1, PA, HA, NP, NA, M, and NS) (11) and Dk/Hk (H5N3) (PB2, PB1, PA, HA, NP, NA, M, and NS) were constructed by PCR. The virulent HA sequence of Dk/Hk (H5N3) was constructed by changing single basic amino acids within the HA cleavage site to multiple basic amino acids (NЈ-TR-CЈ to NЈ-RRKKR-CЈ), as described previously (10).…”
Section: Methodsmentioning
confidence: 99%